2022
DOI: 10.1016/j.jbc.2021.101456
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic atlas of ligand–receptor interactions at the ovine maternal–fetal interface reveals the role of histone lactylation in uterine remodeling

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 119 publications
(162 reference statements)
1
29
0
Order By: Relevance
“…Lactic acid is an important metabolite produced by glycolysis pathway. Recent studies have found that it functions as both a metabolite and a signaling molecule that participates in various physiological and pathological processes [24][25][26][27]. In 2019, it was revealed that lactic acid plays a role in tumor metabolism, immunity, and other biological functions, by mediating lactate modification of proteins and regulating gene expression [12].…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid is an important metabolite produced by glycolysis pathway. Recent studies have found that it functions as both a metabolite and a signaling molecule that participates in various physiological and pathological processes [24][25][26][27]. In 2019, it was revealed that lactic acid plays a role in tumor metabolism, immunity, and other biological functions, by mediating lactate modification of proteins and regulating gene expression [12].…”
Section: Discussionmentioning
confidence: 99%
“…Lactylation is one of the most important ways to exert its biological functions of lactate, and is involved in a series of vital life processes, such as oncogenesis [ 93 ], embryonic development [ 94 ], uterine remodeling [ 95 ], immune disorders [ 96 ], macrophage polarization [ 97 ] and metabolic regulation. To date, only a limited number of studies have examined the role of histone lactylation in regulating central nervous system.…”
Section: The Potential Mechanisms Of Lactate-mediated Exercise-induce...mentioning
confidence: 99%
“…Lactylation is one of the most important ways to exert its biological functions of lactate, and is involved in a series of vital life processes, such as oncogenesis [93], embryonic development [94], uterine remodeling [95],…”
Section: Histone Lactylation: Could This Be the Future Of Exercise Pr...mentioning
confidence: 99%
“…Recently, it has also been claimed that lactylation affects embryogenesis. Yang et al discovered that H3K18la, which is a reflection of histone lactylation in the endometrium, participated in remodeling uterine receptivity ( Yang et al, 2022b ). This finding provided a novel insight for developing potential clinical intervention strategies to increase pregnancy rates following both natural and assisted conception.…”
Section: Lactylation and Diseasesmentioning
confidence: 99%